Collisional charging in the low pressure range of protoplanetary discs. Issue 4 (12th May 2022) - Becker, T; Steinpilz, T; Teiser, J; Wurm, G
ABSTRACT: In recent years, collisional charging has been proposed to promote the growth of pebbles in early phases of planet formation. Ambient pressure in protoplanetary discs spans a wide range from below 10 −9 mbar up to way beyond mbar. Yet, experiments on collisional charging of same material surfaces have only been conducted under Earth atmospheric pressure, Martian pressure and more generally down to 10 −2 mbar thus far. This work presents first pressure dependent charge measurements of same material collisions between 10 −8 and 10 3 mbar. Strong charging occurs down to the lowest pressure. In detail, our observations show a strong similarity to the pressure dependence of the breakdown voltage between two electrodes and we suggest that breakdown also determines the maximum charge on colliding grains in protoplanetary discs. We conclude that collisional charging can occur in all parts of protoplanetary discs relevant for planet formation.